2017
DOI: 10.1016/j.fertnstert.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of transdermal testosterone in postmenopausal women with hypoactive sexual desire disorder: a systematic review and meta-analysis

Abstract: The short-term efficacy in terms of improvement of sexual function and safety of transdermal T in naturally and surgically menopausal women affected by HSDD either on or not on estrogen progestin hormone therapy is evident from this systematic review. The use of transdermal T is associated with increase in androgenic adverse events such as acne but is not associated with any serious adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 51 publications
(94 reference statements)
1
64
0
10
Order By: Relevance
“…A recent meta‐analysis of 7 randomized controlled trials (N = 3035) of a transdermal testosterone patch in women who were naturally or surgically postmenopause and had a diagnosis of hypoactive sexual desire disorder concluded that women using testosterone had significantly more satisfying sexual experiences (including sexual activity, orgasm, and desire) than women using placebo. The meta‐analysis did not find any significant increase in adverse events, although there were increases in acne, hair growth, and site reactions . There is no current testosterone formulation specifically for women.…”
Section: Systemic Hormone Therapy For Menopause‐related Symptomsmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent meta‐analysis of 7 randomized controlled trials (N = 3035) of a transdermal testosterone patch in women who were naturally or surgically postmenopause and had a diagnosis of hypoactive sexual desire disorder concluded that women using testosterone had significantly more satisfying sexual experiences (including sexual activity, orgasm, and desire) than women using placebo. The meta‐analysis did not find any significant increase in adverse events, although there were increases in acne, hair growth, and site reactions . There is no current testosterone formulation specifically for women.…”
Section: Systemic Hormone Therapy For Menopause‐related Symptomsmentioning
confidence: 87%
“…The meta-analysis did not find any significant increase in adverse events, although there were increases in acne, hair growth, and site reactions. 32 There is no current testosterone formulation specifically for women.…”
Section: Testosteronementioning
confidence: 99%
“…These include lifestyle and dietary modifications, supplements, mind–body techniques, and cooling methods (Table ) . The short‐term efficacy of topical treatment such as transdermal testosterone at improving female SD has been reported without any serious adverse events . However, study participants did not have preexisting liver disease or cirrhosis.…”
Section: Management Of Sd and Reproductive Dysfunction In Patients Wimentioning
confidence: 96%
“…Recommendations regarding systemic testosterone therapy for postmenopausal women, in doses that approximate physiological testosterone concentrations for premenopausal women, based on findings from meta-analyses of placebo/comparator-controlled randomized clinical trials [1,16] There are insufficient data to make any recommendations regarding the use of testosterone in premenopausal women for treatment of sexual function or any other outcome (Insufficient).…”
Section: 2mentioning
confidence: 99%